Application of Differentiated Learning in View of Content and Process Aspects to Grade 7 Middle School Students - Novita Sari; Alfiandra Alfiandra; Rike Erlande (CV. Rayyan Dwi Bharata, 2023)
Differentiated learning is still rarely done in the classroom, teachers prefer to do learning with uniformity, even though in reality they face different characteristics of students both in terms of cognitive, psychomotor and affective abilities. Differentiation learning is an option to assist teachers in meeting the needs of diverse students. This study aims to describe the application of differentiated learning in terms of content and process aspects for grade 7 students. This research is a qualitative research. Data collection techniques included interviews, observations and surveys. The research data were analyzed qualitatively, the research subjects were 30 students in class V.II 7. The research location is at SMP Negeri 55 Palembang. The results of the study show that differentiated learning with aspects of content differentiation and process differentiation is an effective way to meet the learning needs of students with different characteristics.